Jilbab Sebagai Etika Busana Muslimah dalam Perspektif Al-Qur’an - Ratna Wijayanti (Universitas Muhammadiyah Magelang, 2017)
Al Qur'an is the holy book of Islam, in which there are many rules of Allah, one of which is the rule about the ethics of Muslim women wearing Jilbab. God's command of the veil contained in the Qur'an always begins with the words of a believing woman. this phrase shows how the hijab's position is based on the faithful women. According to Abdul A'la Al-Maududi as quoted by Quraish Shihab, the basis of all forms of obedience and obedience in Islam is Faith. It is clear that it is faith alone that simply binds a person to remain obedient, obedient to the law of God in all their affairs of life. Therefore, Islam first teaches mankind to believe and strengthen the faith to be imprinted in the hearts of men. It is implanted earlier before taught related to worship, muamalah and morals including in it are morally dressed or veiled contained in al-Qur'an and Al-Hadith. From historical analysis, munasabah analysis, and language analysis of the veil it can be concluded that the veil in general is a wide, loose, and covering the entire body. Meanwhile, the commentators differ on the meaning of